Nanog Predicts Poor Prognosis in Human Pancreatic Cancer and Is Downregulated by QingyihuaJi Formula in Pancreatic Cancer Stem Cells. (17th October 2016) - Gao, Song; Pan, Yan; Song, Libin; Dong, Lei; Weng, Lao I.; Wang, Peng; Hua, Yongqiang; Chen, Zhen; Liu, Luming
Abstract : Qingyihuaji formula (QYHJ), confirmed efficacious in a series of clinical trials, has been applied to human pancreatic carcinoma treatment in Shanghai Cancer Center for years. Recent evidence highlighted that pluripotent stem cells transcription factor Nanog plays a pivotal role in carcinogenesis. However, there is little published information regarding the underlying clinical significance and mechanisms of transcription factor Nanog in pancreatic cancer. In this study, our results indicated that Nanog is overexpressed in human pancreatic cancer stem cells and downregulated by QYHJ, which may contribute to explain the clinical effectiveness of QYHJ and provide advanced pancreatic cancer patients with a new therapeutic option, supporting our hypothesis that the degradation pathway is another mechanism by which QYHJ affects Nanog expression.